1998
DOI: 10.1177/026988119801200309
|View full text |Cite
|
Sign up to set email alerts
|

Haematological safety of antipsychotic drugs

Abstract: Many clinicians have become concerned about the safety of new antipsychotics particularly in view of the association of agranulocytosis with clozapine and of aplastic anaemia with remoxipride. The Committee on Safety of Medicines and Medicines Control Agency 'yellow card' post-marketing surveillance data were analysed for reports of haemopoietic disorders with the 16 antipsychotics in common use. Corrections for relative risk were made in three separate ways: (i) control for degree of use, using Northern Irela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 28 publications
0
19
0
Order By: Relevance
“…By this point, mortality rates are comparable with the risk of developing these side effects with other nonrestricted antipsychotics. For example, it has been reported that chlorpromazine's risk of agranulocytosis is 0.13%, 45 while a recent study estimated the risk for olanzapine in this regard to be 0.15%. 46,47 In summary, clozapine registries and their associated compulsory blood monitoring systems (no blood, no drug) have established their effectiveness in reducing both the incidence of clozapine-induced agranulocytosis and associated mortality rates.…”
Section: Clozapine Agranulocytosis and Mortalitymentioning
confidence: 99%
“…By this point, mortality rates are comparable with the risk of developing these side effects with other nonrestricted antipsychotics. For example, it has been reported that chlorpromazine's risk of agranulocytosis is 0.13%, 45 while a recent study estimated the risk for olanzapine in this regard to be 0.15%. 46,47 In summary, clozapine registries and their associated compulsory blood monitoring systems (no blood, no drug) have established their effectiveness in reducing both the incidence of clozapine-induced agranulocytosis and associated mortality rates.…”
Section: Clozapine Agranulocytosis and Mortalitymentioning
confidence: 99%
“…The ability of new drugs to cause a rare dyscrasia often does not become apparent until the drug is used more widely after licensing, hence such reactions may only be identified during post-marketing studies or after widespread use of the compound (King and Wager, 1998). Clinicians managing a blood dyscrasia should always bear in mind the possibility that it may be drug-induced (Bhatt and Saleem, 2004).…”
Section: Drug-induced Dyscrasiasmentioning
confidence: 99%
“…The risk is highest for both neutropenia and agranulocytosis within the first 6-18 weeks of treatment and most cases occur within the first 6 months (Atkin et al, 1996)-the risk of developing agranulocytosis falls to 0.08% after 1 year of treatment, that is after 1 year the risk is similar to that with chlorpromazine (chlorpromazine agranulocytosis risk up to 0.13%; King and Wager, 1998). The mortality rate due to clozapine-induced agranulocytosis has been estimated at 3-4% of identified agranulocytosis cases (Gerson, 1994).…”
Section: Clozapine and Neutropeniamentioning
confidence: 99%
“…117,121,124 Ten studies related to the incidence of blood dyscrasias such as agranulocytosis and leucopenia. [125][126][127][128][129][130][131][132][133][134] One was a study of NMS, 135 another of venous thromboembolic complications that occurred during clozapine treatment. 136 Five were studies of epilepsy or seizure rates 122,[137][138][139][140] …”
Section: Rare or Long-term Eventsmentioning
confidence: 99%